Comparison of analytical techniques for the identification of bioactive compounds from natural products. Issue 10 (1st July 2016) - Cieśla, Łukasz; Moaddel, Ruin
Abstract : Natural product extracts are a rich source of bioactive compounds. Abstract : Covering: 2000 to 2016 Natural product extracts are a rich source of bioactive compounds. As a result, the screening of natural products for the identification of novel biologically active metabolites has been an essential part of several drug discovery programs. It is estimated that more than 70% of all drugs approved from 1981 and 2006, were either derived from or structurally similar to nature based compounds indicating the necessity for the development of a rapid method for the identification of novel compounds from plant extracts. The screening of biological matrices for the identification of novel modulators is nevertheless still challenging. In this review we discuss current techniques in phytochemical analysis and the identification of biologically active components.